A spin-off cégek szerepe Szeged város gazdasági életében - Vincze-Lendvai, Edina; Gulyás, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The spin-off enterprises are the connection between the university and the market. The one of them, the VOLVO, was founded in 1920. The number of spin-off enterprises has grown since the eighties, primarily in the USA. In our days there are about 3500 firms. We have not any information about the situation in Hungary, but we know that in Szeged there are 36 spin-off enterprises. In our work we presented the BIOPOLISZ Innovation Services Ltd., and its programme. After it we analysed the BIOPOLISZ's spin-off firms.